2007
DOI: 10.1002/eej.20203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of static magnetic field on cell migration

Abstract: SUMMARYThe effect of a magnetic field on cells has long been investigated, but there are few quantitative investigations of the migration of cells. Cell migration is important as one of the fundamental activities of the cell. This study proposes a method to evaluate quantitatively the cell diffusion constant and the effect of a static magnetic field on cell migration. The cell lines are neuroblastoma (NG108-15), fibroblastoma (NIH/3T3), and osteoblastoma (MC3T3-E1). The static magnetic field of 30 or 120 mT is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 12 publications
(11 reference statements)
1
10
0
Order By: Relevance
“…Migration induced by SMF depends on the different cell types. Cell migration was enhanced by 30 and 120 mT of SMF in neuroblastoma and fibroblastoma (Hashimoto, Kawasumi, & Saito, ). In contrast, 5 mT of SMF inhibited the migration of human vascular smooth muscle cells (Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Migration induced by SMF depends on the different cell types. Cell migration was enhanced by 30 and 120 mT of SMF in neuroblastoma and fibroblastoma (Hashimoto, Kawasumi, & Saito, ). In contrast, 5 mT of SMF inhibited the migration of human vascular smooth muscle cells (Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Hashimoto et al . () used SMF to stimulate the migration of various types of cells and found that the migration behaviour was significantly enhanced for high‐activity cells, such as neuroblastoma and fibroblastoma. The present study has similarly found that 0.4‐T SMF promotes the migration of DPSCs towards the injured site (scratch wound) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Hashimoto et al . () reported that SMFs stimulate the migration of certain cell types. A growing body of evidence suggests that the p38 MAPK signalling pathway plays a fundamental role in cell proliferation, cell migration and odontogenesis (Vandomme et al .…”
Section: Introductionmentioning
confidence: 99%
“…transmission of significant information, indicated Hashimoto, (2007, [79]). Wang, (2009, [34]), showed that the exposure of embryonic cells to SMF modulates genes expressions of more than nine signaling networks associated to the inflammatory cytokine IL-6.…”
Section: The Second Effectmentioning
confidence: 99%